Effect of Sweet Purple Potato (Ipomoea batatas L.) Extract and Vitamin C on Endothelial Progenitor Cell Migration in Stable Coronary Disease Patient - Febryanti Hartono; Yudi Her Oktaviono; Djoko Soemantri (Jurnal Kardiologi Indonesia, 2019)
Background: Number and function of Endothelial Progenitor Cells (EPC) are reduced incoronary artery disease (CAD) patient. EPC as progenitor of mature endothelial cell has important role for angiogenesis and neovasculogenesis. Dysfunctional EPC partly because of oxidative stress. Decreasing oxidative stress with antioxidant especially with sweet purple potato extract and vitamin as easily found in Indonesia, may improve EPC migration to ischemic organ in stable CAD patient. Purpose : To analyze effect of sweet purple potato (Ipomoea batatas L.) extract and vitamin C on Endhotelial Progenitor Cell in Stable Coronary Disease patient. Method: This is experimental post-test control group study. Mononuclear cells (MNC) are isolated from peripheral blood of sample, and cultivated in medium for 3 days, immunofluorescence assay with CD34 as a marker for EPC. EPCs divided into sweet purple potato extract group (1 and 25 mcg/mL), vitamin C group (10 and 250 mcg/mL) and control, incubated for 2 days. 5x105 cell taken from each group and place in upper chamber of Transwell system. EPC migration was assessed in lower chamber of Transwell system after 24 hours using automated cell counters. Statistic testing using ANOVA. Results: EPC migration was increased significantly in sweet purple potato extract and vitamin C compared with control (3.03 ± 0.01, 2.15 ± 0.03 vs control 1.21 ± 0.04, p<0.01). Increased dose of sweet purple potato extract and vitamin C shows significantly increased of EPC migration (1.81 ± 0.02 vs1.47 ± 0.04 and 3.03 ± 0.01 vs 2.15 ± 0.03, p<0.01). There is significantly diferentiation between sweet potato purple extract and vitamin C (3.03 ± 0.01 vs 2.15 ± 0.03, p<0.01). Conclusion: Sweet purple potato extract and vitamin C increased EPC migration dose-dependently. Sweet purple potatao extract induces EPC migration better than vitamin C. Keywords: EPC migration, Stable CAD, sweet purple potato extract, vitamin C, antioxidant